2021
DOI: 10.1038/s41598-021-98256-6
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and environmental effects of soybean production in metacoupled systems

Abstract: Human–environment interactions within and across borders are now more influential than ever, posing unprecedented sustainability challenges. The framework of metacoupling (interactions within and across adjacent and distant coupled human–environment systems) provides a useful tool to evaluate them at diverse temporal and spatial scales. While most metacoupling studies have so far addressed the impacts of distant interactions (telecouplings), few have addressed the complementary and interdependent effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 74 publications
1
22
0
1
Order By: Relevance
“…Although, our results show that, about 3.7% of SBM production in 2015 (Ruiz et al, 2020) will be required to farm total finfish species in the study in 2015, this proportion will increase substantially if we considered all fed aquaculture including freshwater and crustacean species. The higher demand on SBM may subsequently increase the direct and indirect impacts of soybean production expansion on land, water and biodiversity (Fearnside, 2002; Gasparri et al, 2016; da Silva et al, 2021; Soutullo et al, 2020). Nevertheless, the critical need to implement alternative protein sources for sustainable mariculture production cannot be overemphasized (Cottrell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although, our results show that, about 3.7% of SBM production in 2015 (Ruiz et al, 2020) will be required to farm total finfish species in the study in 2015, this proportion will increase substantially if we considered all fed aquaculture including freshwater and crustacean species. The higher demand on SBM may subsequently increase the direct and indirect impacts of soybean production expansion on land, water and biodiversity (Fearnside, 2002; Gasparri et al, 2016; da Silva et al, 2021; Soutullo et al, 2020). Nevertheless, the critical need to implement alternative protein sources for sustainable mariculture production cannot be overemphasized (Cottrell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consumers can then be brought closer to producers. Therefore, if society at-large obtains an understanding of the metacoupling framework, this will not only improve research, such as identification of knowledge gaps (Liu and Yang 2013 ), but also assist with the production of new knowledge (Schaffer-Smith et al 2018 ; Dou et al 2020 ; Xu et al 2020a ; da Silva et al 2021 ), and the development and adoption of more effective sustainability policies (Liu et al 2018b ). Such an understanding may come from the incorporation of the framework into education curricula, from K-12 to graduate school levels, with a direct identification of individual coupled human and-natural systems, the flows within and between those systems, and the causes and effects of those flows.…”
Section: Towards a Sustainable Metacoupled Worldmentioning
confidence: 99%
“…The term LULC change refers to the transformation of the natural environment or wilderness into a built environment, such as elds, pastures, industrialization, settlement, agricultural practices, etc (Abbas et al 2010). It has been demonstrated that LULC changes have signi cant impacts on the environment at the local, regional, and global levels (Kilic et al 2006; Yaro and Abdulrashid 2017; da Silva et al 2021). LULC change is a cause and consequence of global environmental change (Song et al 2018).…”
Section: Introductionmentioning
confidence: 99%